2018
DOI: 10.4174/astr.2018.95.5.267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of 1,000 consecutive cases of liver transplantation: a single center experience

Abstract: PurposeThe aim of this study was to analyze survival outcomes in 1,000 consecutive liver transplantations (LTs) performed at a single institution from 1993 to April 2017.MethodsThe study population was divided into 2 groups based on donor type: deceased donor LT (DDLT; n = 181, 18.1%) and living donor LT (LDLT; n = 819; 81.9%), and into 3 periods based on the number of cases (first 300 cases, middle 300 cases, last 400 cases).ResultsInfection was the most common cause of death, accounting for 34.8% (95 of 273)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Kusakabe et al (16) found that the three leading causes of death after LT were sepsis, graft failure, and pulmonary complications. Kwak et al (17) reported that the first three causes of death for recipients after LT were infection, recurrence of hepatocellular carcinoma, and graft failure, accounting for 34.8%, 18.3%, and 15.0% of cases, respectively. Different incidences of infection after LT have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Kusakabe et al (16) found that the three leading causes of death after LT were sepsis, graft failure, and pulmonary complications. Kwak et al (17) reported that the first three causes of death for recipients after LT were infection, recurrence of hepatocellular carcinoma, and graft failure, accounting for 34.8%, 18.3%, and 15.0% of cases, respectively. Different incidences of infection after LT have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, postoperative outcomes are gradually improving because of development of surgical skills, medical treatment, and supporting resources. Recent study showed 74.7% patient survival at 5-year in 1,000 cases of LT in single center [1].…”
Section: Introductionmentioning
confidence: 98%
“…Due to the absolute shortage of brain-dead organ donors, the opportunity arises only in critically ill patients with a MELD score of 40 or more. Currently, the number of brain-dead organ donors per million in South Korea is 8.68, which is very low compared to 48.9 in Spain and 36.88 in the United States [ 15 16 ]. This serious shortage of brain-dead donors appeared to be a phenomenon in which patients with high severity were mainly selected for DDLT after the introduction of the MELD system [ 17 ].…”
Section: Discussionmentioning
confidence: 99%